1996
DOI: 10.1002/ctpp.2150360505
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Broadening and Magnetic Field Effects on the Balmer Lines Emitted at the Edge of a Tokamak Plasma

Abstract: Profiles of the Balmer lines D,(H,), Db(Hs) and D, (H,) have been measured in the scrape-off layer and within the edge of the TEXTOR (upgrade) plasma, under Ohmic conditions and with neutral-beam injection. Each line profile shows a strong Zeeman effect in the vicinity of line centre, and a marked central dip when mainly the ( I components are observed. The line core evidently originates from cold atoms in the edge plasma, excited in the course of molecular dissociation, while the broad pedestal on which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
132
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(139 citation statements)
references
References 34 publications
7
132
0
Order By: Relevance
“…Yet for neutral emitters, asymmetric line profiles due to the Stark effect are predicted [4]. However, for further explanations of the observed phenomena in future work, one should evaluate effects associated with internally generated micro electromagnetic fields [4][5][6][7]24,33] in nanomaterial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet for neutral emitters, asymmetric line profiles due to the Stark effect are predicted [4]. However, for further explanations of the observed phenomena in future work, one should evaluate effects associated with internally generated micro electromagnetic fields [4][5][6][7]24,33] in nanomaterial.…”
Section: Discussionmentioning
confidence: 99%
“…(I) Self-reversal is characterized by a large dip at the central wavelength [33], (II) Self-absorption, and (III) Asymmetries.…”
Section: Discussionmentioning
confidence: 99%
“…͑18 and 30 allowed, 2 and 4 ⌬J forbidden͒. [5][6][7] The corresponding perturbed line strengths are calculated according to the method described in Ref. 23.…”
Section: Analysis Of the Zeeman Profiles And Discussionmentioning
confidence: 99%
“…1,2 Its quantitative estimate is required for the purpose of evaluating the particle fueling rate and controling the recycling neutrals in the long pulse discharge operation. 3,4 Information on neutral atoms has been obtained from spectroscopic measurements of the Zeeman ͑Paschen-Back͒ split profiles of lines emitted from the divertor or the periphery region in TEXTOR ͑Tokamak-Experiment for Technology Oriented Research͒, [5][6][7][8] JT-60U ͑Japan atomic energy research institute Tokamak-60 Upgrade͒, 9,10 Alcator C-Mod, [11][12][13] Doublet III-D, [14][15][16] ASDEX-U ͑Axially Symmetric Divertor Experiment Upgrade͒, 17,18 Tore Supra, 19,20 TRIAM-1M ͑Torus of Research Institute for Applied Mechanics͒ ͑Ref. 21͒ for hydrogen/deuterium, and in LHD ͑Large Helical Device͒ for helium.…”
Section: Introductionmentioning
confidence: 99%
“…Line shape measurements of atomic hydrogen emissions have provided information about velocity distributions of the atoms. J. D. Hey et al measured the Balmer series line shapes in TEXTOR [1]. They found that the velocity distributions of the excited hydrogen or deuterium atoms were in non-thermal.…”
Section: Introductionmentioning
confidence: 99%